ChemVirtual Lab: Gamified Learning Experience on Reaction Rate Topic to Improve Learning Outcomes - Rokhmawati, Retno Indah; Sholihah, Tuffahati; Sahasika Laksmana, Kumara; Pramudita, Rizky; Sambata Sarborn, Ibrahim; Hendra Brata, Adam (Journal of Information Technology and Computer Science, 2023)
This study aims to improve student learning outcomes through gamification of chemical learning media. As we know that chemical material, especially reaction rates, is abstract in nature, so it is quite difficult to convey this concept to students. Because the measured compounds vary greatly in terms of concentration, this material has complex features. However, in real conditions, students have limited access to chemical laboratory equipment, so learning media is needed that considers aspects of people, problems, and context to provide learning experiences like real laboratories.  ChemVirtual Lab is a learning tool that combines immersive learning experiences with game elements to improve students' learning outcome by allowing them to direct their own learning and inspiring them to think creatively and innovatively. The primary model in this study is the ASSURE learning media development paradigm. Evaluation of the usage of educational media was conducted to ascertain factors of satisfaction and usefulness with 3 media experts and 3 material experts. According to the six experts' test results, it would be possible to implement the media. Then the media was implemented to 62 high school students who were studying Rate of Reaction material. The Paired Sample T-Test was used to examine the effectiveness of the media's implementation, and the results revealed significant differences in learning outcomes as well as a tendency for post-test scores to rise above pre-test results.